PERKEMBANGAN KONSEP PENURUNAN TAHANAN TARIK PADA PENGEMBANGAN DISAIN BAJAK SUBSOIL GETAR - Yazid lzmi lntara; Radite Praeko Agus Setiawan (PERTETA, 2007)
Abstract From many experiments with different kinds of tiIIage tools it is well known that an oscilating or vibrating movement of a tool can have a considerable influence on the draft required. Subsoiler represent tools of deep tillage, the function of subsoil plough to cutting deep tillage and to breaking hardpan soil. The hardpan soil can hinder drainage, aeration and pursue spreading of the soil nutrition. Therefore in split/cut the hardpan layer require by big enough of energy. This operation requires heavy-duty tractor because of high draft consumption, especially for breaking subsoil up to depth of 50 cm. Vibratory technique is one of the methods, which could be applied in order to reduce draft. On the other hand reduced draft can used by vibration, mechanism of vibration exploitedly with rotation of PTO changed become translation movement. However that vibration can greatly reduce the draft force needed, to pull a blade or tine trough soil, but this can only be achieved at the expense of an increase in the total powor consumed. Diterima: 12 Pebruari 2007, Disetujui:. 3 Mei 2007